“Brazil power and multinational corporation”: brazilian multinational corporations, foreign policy and the international insertion of Brazil: an analysis based on the contributions of Robert Gilpin - Actis, Esteban (2013)
The first decade of the XXI century evidenced transformations in the international order’s financial dimension due to the growth in the so-called emerging powers. An indicator of such phenomenon is the emergence of multinational corporations from the developing world - MNC Latecomers-, turning certain countries, as is the case of Brazil, into net issuers of Foreign Direct Investment flows. In this sense, this paper analyzes the impact that the emergence and consolidation of Brazilian multinational corporations has had since 2003 until now on the foreign policy and the international insertion of Brazil (and vice versa), taking into consideration Robert Gilpin’s classical work, “U.S. power and multinational corporation: the political economy of foreign direct investment.” Gilpin’s framework shall be useful for empirical contrast of this study case.